Necrosis of an ectopic testicle in a child - A. Zh. Kadyrkulov; R. N. Nakipov; M. N. Nasybullin (Лечащий Врач)
Cryptorchidism is dangerous for possible complications that affect both reproductive health and the state of organs. In patients with bilateral cryptorchidism, infertility as a complication reaches 80%. From a clinical point of view, the most convenient classification of cryptorchidism is its division into cases with palpable and non-palpable testes; clinical tactics is determined by the location and presence of the testicles as such. In about 50% of cases, non-palpable testes are located in the peritoneal cavity, at the inner opening of the inguinal canal, or in the canal itself; in 30% they are atrophic or rudimentary; in 20% of cases, testicular agenesis is observed. Possible causes of testicular absence are agenesis and atrophy after intrauterine torsion. Torsion of an ectopic testicle is extremely rare in pediatric surgery. This clinical example describes torsion, necrosis of an ectopic testicle in order to attract attention, remind pediatric surgeons, urologists, pediatricians of polyclinics, as well as parents of patients about the existence of this disease and the development of alertness, careful observation of children with an undescended testicle, since late diagnosis can to its necrosis.